CHARACTERISTICS OF BURYAT CHILDREN'S SOCIALIZATION IN THE TRADITIONAL CULTURE - Turkmen, Mehmet; Ziyagil, Mehmet Akif (Univ Catolica Petropolis, 2022)
The aim of this study was to characteristics of Buryat children's socialization in the traditional culture. In the system of parenting values, the responsibility of parents towards family-relatives in the formation of the child's personality is emphasized. Multi-childhood in the family is supported by faith in the rebirth of the soul, the adoption of a special mission of the emergence of the child, the tradition of giving children to childless relatives. Socialization mechanisms in the nomadic community, age transition (age initiations) and ceremonies, transition to working life, gender sociology. The research is based on an axiological approach: the traditions of the ancestral culture served as the ideals of parenting, in which the main principle is the value attitude towards the child. Based on the theoretical analysis of Buryats' ethnographic data, the specificity and mechanisms of socialization of children in traditional culture were determined. The application of comparative-matched analyzes made it possible to reveal the similarities and differences in determining the childhood boundaries and educational traditions of Turkish-Mongolian speaking peoples. The modeling method made it possible to embody empirical research data and confirm the age- related periodization of childhood in Buryats. The practices and mechanisms of children's socialization were analyzed based on traditions and ritual actions that enable the child to transition to a new stage of growth. It turns out that the main environment of socialization of the individual in the childhood stage is a family or a group associated with the family. The system of traditional educational values that defines Buryat's behavioral models, determined the understanding of his Self in social relations, his early inclusion in business life.
Keywords: Traditional Culture; Educational Values; Age Initiations; Socialization; Transitional Customs; Family Traditions